Metagenomics-based tracing of genetically modified microorganism contaminations in commercial fermentation products - Jolien D’aes; Marie-Alice Fraiture; Bert Bogaerts; Yari Van Laere; Sigrid C.J. De Keersmaecker; Nancy H.C. Roosens; Kevin Vanneste (Food Chemistry: Molecular Sciences)
Genetically modified microorganisms (GMM) are frequently employed for the production of microbial fermentation products such as food enzymes. Although presence of the GMM or its recombinant DNA in the final product is not authorized, contaminations occur frequently. Insight into the contamination source of a GMM is of crucial importance to allow the competent authorities to take appropriate action. The aim of this study was to explore the feasibility of a metagenomic shotgun sequencing approach to investigate microbial contamination in fermentation products, focusing on source tracing of GMM strains using innovative strain deconvolution and phylogenomic approaches. In most cases, analysis of 16 GMM-contaminated food enzyme products supported finding the same GM producer strains in different products, while often multiple GMM contaminations per product were detected. Presence of AMR genes in the samples was strongly associated with GMM contamination, emphasizing the potential public health risk. Additionally, a variety of other microbial contaminations were detected, identifying a group of samples with a conspicuously similar contamination profile, which suggested that these samples originated from the same production facility or batch. Together, these findings highlight the need for guidelines and quality control for traceability of these products to ensure the safety of consumers. This study demonstrates the added value of metagenomics to obtain insight in the microbial contamination profiles, as well as their underlying relationships, in commercial microbial fermentation products. The proposed approach may be applied to other types of microbial fermentation products and/or to other (genetically modified) producer strains.